2018
DOI: 10.1021/acsami.7b17902
|View full text |Cite
|
Sign up to set email alerts
|

Activating TiO2 Nanoparticles: Gallium-68 Serves as a High-Yield Photon Emitter for Cerenkov-Induced Photodynamic Therapy

Abstract: The classical photodynamic therapy (PDT) requires external light to activate photosensitizers for cancer treatment. However, limited tissue penetration of light has been a long-standing challenge for PDT to cure malignant tumors in deep tissues. Recently, Cerenkov radiation (CR) emitted by radiotracers such as F-fluorodeoxyglucose (F-FDG) has become an alternative and promising internal light source. Nevertheless, fluorine-18 (F-18) only releases 1.3 photons per decay in average; consequently, injection dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 54 publications
2
96
1
3
Order By: Relevance
“…The CR spectrum from the model followed the Frank-Tamm equation (number of photons a 1/l 2 ), and the number of photons generated also matched that in a previous report (28). The model was compared with 2 different experimental studies (15,23). The experiments revealed a change in tumor cell viability as a function of the 18 F-FDG dose; this change was then converted into the ROS concentration using a constant scaling factor, and this ROS concentration was compared with the ROS concentration predicted from the model using the experimental parameters from those studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The CR spectrum from the model followed the Frank-Tamm equation (number of photons a 1/l 2 ), and the number of photons generated also matched that in a previous report (28). The model was compared with 2 different experimental studies (15,23). The experiments revealed a change in tumor cell viability as a function of the 18 F-FDG dose; this change was then converted into the ROS concentration using a constant scaling factor, and this ROS concentration was compared with the ROS concentration predicted from the model using the experimental parameters from those studies.…”
Section: Discussionmentioning
confidence: 87%
“…Kamkaew et al (16) reported a system with a 89 Zr radionuclide (Cerenkov radiation source) and chlorin e6 (photocatalyst) and demonstrated its advantage in ROS generation through CR. Two radionuclides-68 Ga and 18 F-were recently studied for their cellular uptake and effectiveness in cancer treatment (23,24).…”
mentioning
confidence: 99%
“…Forexample,while 18 Fand 64 Cu give 1.32 and 0.56 photons per decay,respectively,higher energy b emitters such as 90 Yand 68 Ga produce 47.3 and 33.9 photons per decay, respectively. [9,58] Thei nfluence of the isotope choice was tested by Duan et al, [58] who reported the first use of 68 Ga as aC Rs ource to activate oxide (TiO 2 )N Ps for PDT.T he authors compared the PDT efficiencyo ft he same nanoparticles when activated by CR from 18 F-FDG or 68 Ga-BSA. In vitro studies indicated that despite the cellular uptake of F-FDG being much higher than that of 68 Ga-BSA, 68 Ga-BSA promoted more efficient growth suppression.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Although the studies mentioned above demonstrated the applicability of CR-PDT,t he intensity of the photons generated was still much lower than those of excited by external sources. [58] In ar ecent publication, we introduced an ew strategy to improve the therapeutic efficacy of CR-PDT [74] by overcoming both the depth and external light dependence of traditional PDT.I nt his strategy, (Zn 0.4 Mn 0.6 )Fe 2 O 4 nanoparticles (MNPs) were guided to the desired tissue by an external magnetic field. TheMNPs were labeled chelator-free with 89 Zr as as ource of CR as well as conjugated with porphyrin molecules of meso-tetrakis(4carboxyphenyl)porphyrin (TCPP) to be excited for ROSmediated tumor-cell damage (Figure 15 a).…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…0.56 Photonen pro Zerfall produzieren, liefern höherenergetische β‐Emitter, wie 90 Y und 68 Ga, 47.3 bzw. 33.9 Photonen pro Zerfall . Der Einfluss des gewählten Isotops wurde von Duan und Mitarbeitern evaluiert, die erstmals den Einsatz von 68 Ga als CR‐Quelle zur Aktivierung oxidischer NPs (TiO 2 ) für die PDT publizierten.…”
Section: Bildgebung Und Therapeutische Anwendungenunclassified